A Study on the Mordant Activity of Emblica officinalis (Indian Goosberry) in Dyeing of Cotton Fabrics with Direct Dye - Jayanthi, C. (Asian Journal of Chemistry, 2010)
This study was carried out to determine the mordant activity of Emblica officinalis in dyeing of cotton fabrics with direct dye. For this purpose dried fruits of Emblica officinalis (Indian Goosberry) cultivated at 5 different places were collected. To find best quality sample which were subjected to qualitative analysis of phytochemicals such as alkaloids, carbohydrates fixed oil and fats, saponin, tannin and phenols, gums and mucilages and quantitative analysis of one of the phytochemical present in it. In the five samples, tannin was estimated by colorimetric method. Best quality sample was used as mordant at different concentrations, different pH and temperatures in dyeing process of cotton with direct dye. It was concluded that Emblica officinalis acts as good mordant in equal concentration with water, in neutral condition and at higher temperature in dyeing of cotton with ATUL direct sky blue.